Crystal structure of solifenacin hydrogen succinate, C23H27N2O2(HC4H4O4). Issue 3 (12th August 2015) - Kaduk, James A.; Reid, Joel W.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of solifenacin hydrogen succinate [C23 H27 N2 O2 (HC4 H4 O4 )] has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Solifenacin hydrogen succinate crystallizes in space group P 21 (#4) with a = 6.477 03(2), b = 7.830 95(2), c = 23.848 72(7) Å, β = 90.2373(3)°, V = 1209.63(1) Å 3, and Z = 2. The hydrogen succinate anions form a chain linked by strong hydrogen bonds parallel to the a -axis. Discrete N–H···O hydrogen bonds lie on the sides of this chain, resulting in a layer parallel to the ab -plane rich in hydrogen bonds. Halfway between these layers the molecules meet in a herringbone packing of aromatic rings. The powder pattern has been submitted to ICDD for inclusion in future releases of the Powder Diffraction File™.